Mortality from external causes in Russia over half a century - Ekaterina Kvasha; Tatiana Kharkova; Valeriy Yumaguzin (Демографическое обозрение, 2017)
The article discusses long-term mortality trends (since 1956) from external causes of death in Russia. Russia has long lagged behind developed countries in this domain. The level of mortality from external causes of death remains high and its structure is still archaic with large contribution of homicides, alcohol poisoning and injuries of undetermined intent.